PENGARUH ADVERTISING BERBASIS MEDIA SOSIAL TERHADAP MINAT BELI ULANG KONSUMEN DI RESTORAN PIPE AND BARREL SURABAYA - Marcus Remiasa; Olivia Gisena Santoso; Evelyn Setiadi (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
The most often used Social media are instagram, facebook, and twitter. The main activities in social media are viewing news, uploading photos/video, and giving comment to other member. Conditions such as these is used by cafe or restaurant as a promotional tool, and the main promotion activity is advertising. This study was conducted to determine the influence of advertising which are personal relevance, online interactivity, message and brand familiarity based on social media to re-purchasing intentionat Pipe and Barrel Restaurant, Surabaya. This type of research is quantitative causal with multiple linear regression analysis was used to determine the influence of independent variables on the dependent variable. The results shows personal relevance is the only variabel that have positive and significant influence and become the most dominant variable that gives influence onre-purchasing intention. Online interactivity and brand familiarity havepositive effect but not significant to the re-purchasing intention. Message has negative and not significant effect on the re-purchasing intention. Simultaneously the four variables have positive and significant effect on the re-purchasing intention at Pipe and Barrel Restaurant, Surabaya.